Die Revolution, der Schrecken und das Neue. Konzepte von Legitimität und historischer Gewalt in deutschen Revolutionsdramen um 1800 - Eke, Norbert Otto (Literatur und Erfahrungswandel 1789-1830. Beiträge des 2. Internationalen Corvey-Symposions 8.-12. Juni 1993 in Paderborn)

Eine Bibliothek von Basisdiensten für Parallelrechner: Routing, Synchronisation, gemeinsamer Speicher - Wachsmann, Alf

Der evangelische Kirchenbau im 19. Jahrhundert, die Eisenacher Bewegung und der Architekt Christian Friedrich von Leins - Seng, Eva- Maria
Rezensionen (Auswahl) in: - architectura Bd. 27, 1997, Heft 2, S. 221-228 von Elisabeth Spitzbart - Blätter für württembergische Kirchengeschichte 96. Jg. 1996, S. 253f.von Rainer Lächele - Etudes Theologiques Et Religieuses (Montpellier) 1997, 3, S. 490-491 von Bernard Reymond

Existenzgründung - Kremer, H.-Hugo (Meisterprüfung - Lernen für die Praxis - Unternehmensführung 1)

Existenzgründung - Kremer, H.-Hugo (Meisterprüfung - Lernen für die Praxis - Unternehmensführung 1)

Application of Clustering Techniques to Mixture Density Modelling for Continuous-Speech Recognition - Dugast, Christian; Beyerlein, Peter; Haeb-Umbach, Reinhold (ICASSP, Detroit)
Clustering techniques have been integrated at different levels into the training procedure of a continuous-density hidden Markov model (HMM) speech recognizer. These clustering techniques can be used in two ways. First acoustically similar states are tied together. It will help to reduce the number of parameters but also allow to train otherwise rarely seen states together with more robust ones (state-tying). Secondly densities are clustered across states, this reduces the number of densities while at the same time keeping the best performances of our recognizer (density-clustering). We have applied these techniques both to word-based small-vocabulary and phoneme-based large-vocabulary recognition tasks. On the WSJ task, we could achieve a reduction of the word error rate by 7%. On the TI/NIST-connected digit task, the number of parameters was reduced by a factor 2-3 while keeping the same string error rate.

Continuous speech dictation - From theory to practice - Steinbiss, Volker; Ney, Hermann J.; Essen, Ute; Tran, Bach Hiep; Aubert, Xavier L.; Dugast, Christian; Kneser, Reinhard; Meier, Hans Günter; Oerder, Martin; Haeb-Umbach, Reinhold; Geller, Dieter; Hoellerbauer, W.; et al. (Speech Communication)
This paper gives an overview of the Philips research system for phoneme-based, large-vocabulary, continuousspeech recognition. The system has been successfully applied to various tasks in the German and (American) English languages, ranging from small vocabulary tasks to very large vocabulary tasks. Here, we concentrate on continuousspeech recognition for dictation in real applications, the dictation of legal reports and radiology reports in German. We describe this task and report on experimental results. We also describe a commercial PC-based dictation system which includes a PC implementation of our scientific recognition prototype. In order to allow for a comparison with the performance of other systems, a section with an evaluation on the standard Wall Street Journal task (dictation of American English newspaper text) is supplied. The recognition architecture is based on an integrated statistical approach. We describe the characteristic features of the system as opposed to other systems: 1. the Viterbi criterion is consistently applied both in training and testing; 2. continuous mixture densities are used without tying or smoothing; 3. time-synchronous beam search in connection with a phoneme look-ahead is applied to a tree-organized lexicon.

Quasi-particle band structure of C(111)2 × 1 and C(100)2 × 1 surfaces - Kress, Clemens; Fiedler, Marion; Schmidt, Wolf Gero; Bechstedt, Friedhelm (Surface Science)

III-V(110)/Sb(1 ML): structural and dynamical properties - Schmidt, Wolf Gero; Srivastava, G.P. (Surface Science)

A Formal Definition of an Abstract VHDL'93 Simulator by EA-Machines - Börger, Egon; Glässer, Uwe; Müller, Wolfgang (Semantics of VHDL)
We present a rigorous but transparent semantic definition for VHDL corresponding to the IEEE VHDL’ 93 standard [68, 9, 84]. Our definition covers the full behavior of signal and variable assignments as well as the behavior of the various wait statements including delta, time, and postponed cycles. We consider explicitly declared signals, ports, local variables, and shared variables. Our specification defines an abstract VHDL ’ 93 interpreter in the form of transition rules for an evolving algebra machine (EA-Machine) [60]. It faithfully reflects and supports the view of simulation given in the IEEE VHDL ’ 93 standard language reference manual. The definition can be understood without any prior formal training. We illustrate our definition by running the example VHDL program set out in the Introduction to this volume.
Keywords: Transition Rule Formal Verification Variable Assignment Kernel Process Simulation Cycle

Orientation and Motion of Tetrahydrofuran in Graphite Intercalation Compounds: Proton NMR Studies of Cs(THF)1.3C24 and K(THF)2.5C24 - Schmidt, Claudia; Rosen, M. E.; Caplan, D. F.; Pines, A.; Quinton, M. F. (The Journal of Physical Chemistry)
Keywords: Physical and Theoretical Chemistry; General Engineering

Shear-Induced Alignment of a Hexagonal Lyotropic Liquid Crystal as Studied by Rheo-NMR - Lukaschek, Michail; Grabowski, David A.; Schmidt, Claudia (Langmuir)
Keywords: Electrochemistry; Spectroscopy; Surfaces and Interfaces; Condensed Matter Physics; General Materials Science

Amphiphilic liquid-crystalline networks — phase behavior and alignment by mechanical fields - Fischer, Peter; Schmidt, Claudia; Finkelmann, Heino (Macromolecular Rapid Communications)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Transforming SDL Diagrams Into a Complete Visual Representation - Lehrenfeld, Georg; Müller, Wolfgang; Tahedl, C. (Proceedings of Symposium on Visual Languages)
We investigate a translation of SDL diagrams into the complete visual representation of Pictorial Janus (PJ) programs in order to analyze the specification by visual debugging and animation. We additionally introduce timing concepts to PJ (Timed PJ) for a mapping of the SDL timing statements. The concepts transforming SDL interaction and process diagrams into Timed PJ are outlined by an example sketching the transformation of an Ethernet CSMA/CD protocol specification.
Keywords: Animation; Timing; Debugging; Ethernet networks; Multiaccess communication; Protocols; Computer languages; Prototypes; Environmental management; Visualization

Azimuthal Anchoring Energy in Photoinduced Anisotropic Films - Vorflusev, Valery P.; Kitzerow, Heinz-Siegfried; Chigrinov, Vladimir G. (Japanese Journal of Applied Physics)
Most electrooptic effects in liquid crystals require a uniform orientation of the director at the glass substrates. A new method to produce suitable alignment layers is based on the creation of anisotropic polymer films by photopolymerization with linearly polarized light. In the present paper we report on measurements of the anchoring strength of these photo-induced anisotropic films. Using a wedge-cell technique, we find an azimuthal anchoring energy of W ϕ ≈2.3·10 -6 J/m 2 .
Keywords: General Physics and Astronomy; General Engineering

Quantum beats from biexcitons in narrow quantum wells: polarization and density dependence - Meier, Torsten; Albrecht, T.F.; Schulze, A.; Koch, M.; Bott, K.; Feldmann, J.; Stolz, W.; Kuhl, J.; Mayer, E.J.; Koch, S.W.; Göbel, E.O.; Cundiff, S.T. (Quantum Electronics and Laser Science Conference)
Transient four-wave mixing (TFWM) has been extensively used during the last few years to study exciton dynamics in semiconductors and in semiconductor heterostructures. These studies have provided significant insight into exciton dynamics in both ordered and disordered systems. There are, nevertheless, still certain aspects of the excitonic TFWM response that are not completely understood. In particular, a complete understanding of the polarization and intensity dependences of the signai strength, the decay of the time-integrated signal, and the temporal characteristics of the time-resolved signal has proven elusive. Recent theoretical and experimental work has indicated that exciton-exciton interactions are important.1·2 Such interactions include incoherent processes, such as excitation-induced dephasing, and the formation of biexcitons. Additionally, some of the phenomena result from disorder, making them sample dependent.

Polarization dependence of quantum beats between light-hole and heavy-hole excitons in GaAs quantum wells - Meier, Torsten; Kuhl, J.; Mayer, E.J.; Smith, G.O.; Bott, K.; Heuckeroth, V.; Thomas, P.; Koch, M.; Hey, R.; Ploog, K. (Quantum Electronics and Laser Science Conference)
The appearance of quantum beats (QBs) between heavy-hole (hh) and light-hole (lh) excitons in GaAs quantum wells (QWs) has been observed in many degenerate-four- wave-mixing (DFWM) experiments with subpicosecond optical pulses. Although the variation of the beat amplitude and phase with polarization of the incident pulses was recognized early on, a consistent theoretical interpretation of exciton coherence for the case of simultaneous excitation of hh and lh excitons is still missing.

Entwurf eines Drehbuchs für eine Hypermedia-Arbeitsumgebung zum sozialen Lernen - Herzig, Bardo; Mütze, Ch.; Greiff, S.

The Design Process for Conventional and Neural Controllers - a Case Study - Nowinski, Günther; Trächtler, Ansgar; Lafuente Jorge, Ruben (Proc. 2. Intern. Conf. Intelligent Systems Engineering)

Berücksichtigung von Datenschutzaspekten in einem bevölkerungsbezogenen Krebsregister - Thoben, Wilfried; Appelrath, Hans-Jürgen; Rettig, Jens; Sauer, Stefan (Proceedings of the conference on Medizin und Information, Biometrie und Epidemiologie (GMDS 1994), Dresden (Germany))
Die Pilotphase 1993/ 94 zum Aufbau eines Niedersächsischen Krebsregister untersucht das im Entwurf des Bundeskrebsregistergesetzes vorgesehen Modell für ein bevölkerungsbezogenes Krebsregister. Darin werden die Krebsmeldungen in einer Vertrauensstelle erfaßt und die personenidentifizierenden Daten vor der Übermittlung an die Registerstelle anonymisiert, wo sie dann zu einem bevölkerungsbezogenen Krebsregister verdichtet und epidemiologischer Forschung zur Verfügung gestellt werden ([1], [2], [3]). Dieses sogenannte „Michaelis“-Modell erlaubt eine bevölkerungsbezogene Registrierung von Krebsfällen unter Berücksichtigung datenschutzrechtlicher Aspekte („Informationelles Selbstbestimmungsrecht“) der einzelnen Betroffenen. In vier Teilprojekten werden dabei in der Modellregion Weser-Ems die Integration krebsregistrierender Einrichtungen, die Chiffrierung/ Dechiffrierung von Krebsmeldungen, der Abgleich anonymisierter Meldungen in der Registerstelle und die Entwicklung eines epidemiologischen Informationssystem betrachtet ([4], [5]).

Optical Modelling, Simulation and Improvement of PV Module Encapsulation - Krauter, Stefan; Hanitsch, Rolf; Campbell, P.; Wenham, S.R. (Proceedings of the 12th European Photovoltaic Solar Energy Conference, Amsterdam (Niederlande), 11.–15. April 1994, Band 2, S. 1198–1201)

Simulation Tool for Prediction and Optimization of Output Power Considering Thermal and Optical Parameters of PV Module Encapsulation - Strauss, Philipp; Onneken, K.; Krauter, Stefan; Hanitsch, Rolf (Proceedings of the 12th European Photovoltaic Solar Energy Conference, Amsterdam (Niederlande), 11.–15. April 1994, Band 2, S. 1194–1197.)

Einfluß optischer und thermischer Parameter auf den Tageswirkungsgrad von photovoltaischen Modulen - Krauter, Stefan; Hanitsch, Rolf (Neuntes Internationales Sonnenforum, Berlin (Deutschland), 28. Juni – 1. Juli 1994, S. 495–502)

Symmetry of Attractors and the Karhunen-Loève Decomposition - Dellnitz, Michael; Golubitsky, Martin; Nicol, Matthew (Trends and Perspectives in Applied Mathematics)

An Overview of the Philips Research System for Large Vocabulary Continuous Speech Recognition - Ney, Hermann; Steinbeiss, Volker; Haeb-Umbach, Reinhold; Tran, Bach Hiep (International Journal on Pattern Recognition and Artificial Intelligence)
This paper gives an overview of a research system for phoneme based, large vocabulary continuous speech recognition. The system to be described has been applied to the SPICOS task, the DARPA RM task and a 12000 word dictation task. Experimental results for these three tasks will be presented. Like many other systems, the recognition architecture is based on an integrated statistical approach. In this paper, we describe the characteristic features of the system as opposed to other systems: (1) The Viterbi criterion is consistently applied both in training and testing. (2) Continuous mixture densities are used without any tying or smoothing; this approach can be viewed as a sort of statistical template matching. (3) Time-synchronous beam search is used consistently throughout all tasks; extensions using a tree organization of the vocabulary and phoneme lookahead are presented so that a 12000 word task can be handled.

Alexander Rüstow's Thesis, Beitrag für russell-l@mcmail.cis.mcmaster am 17. Juni 1994 [Abdruck: Rüstow’s Thesis on Russell’s Paradox, History of Logic Newsletter, Nr. 13 (September–Oktober 1994), 2–3] [revidierte Fassung: Rüstow’s Thesis on Russell’s Paradox”, Modern Logic 5 (1995), 167–169] - Peckhaus, Volker
[Abdruck siehe 7.13, revidierte Fassung 4.18]

"Weibsfauna". Zur Koinzidenz von Tiergeschichte und Pornographie am Beispiel von Bambi und Josefine Mutzenbacher - Öhlschläger, Claudia; Schmidt, Dietmar (Hofmannsthal-Jahrbuch 2)

A Doubly Branched Nonionic Oligooxyethylene V-Amphiphile: Effect of Molecular Geometry on Liquid-Crystalline Phase Behavior, 3 - Kratzat, Krystyna; Schmidt, Claudia; Finkelmann, Heino (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Simultaneous Measurement of Shear Viscosity and Director Orientation of a Side-Chain Liquid-Crystalline Polymer by Rheo-NMR - Grabowski, D. A.; Schmidt, Claudia (Macromolecules)
Keywords: Materials Chemistry; Inorganic Chemistry; Polymers and Plastics; Organic Chemistry

Nematic elastomers beyond the critical point - Disch, Stefan; Schmidt, Claudia; Finkelmann, Heino (Macromolecular Rapid Communications)
Keywords: Materials Chemistry; Polymers and Plastics; Organic Chemistry

Conformational order of amphiphilic chain molecules in lyotropic liquid-crystalline phases - Schnepp, Werner; Schmidt, Claudia (Berichte der Bunsengesellschaft für physikalische Chemie)
Keywords: General Chemical Engineering

Electro-optic effect in polymer-dispersed cholesteric liquid crystals with medium chirality - Behrens, Ulrike; Kitzerow, Heinz-Siegfried; Chilaya, Gouram (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Bistability in polymer‐dispersed ferroelectric liquid crystals - Molsen, Henning; Kitzerow, Heinz-Siegfried (Journal of Applied Physics)
Keywords: General Physics and Astronomy

Polymer-dispersed cholesteric liquid crystals - Crooker, Peter P.; Kitzerow, Heinz-Siegfried; Xu, F. (Liquid Crystal Materials, Devices, and Applications III)

Polymer-dispersed liquid crystals From the nematic curvilinear aligned phase to ferroelectric films - Kitzerow, Heinz-Siegfried (Liquid Crystals)
Keywords: Condensed Matter Physics; General Materials Science; General Chemistry

Director configurations of nematic-liquid-crystal droplets: Negative dielectric anisotropy and parallel surface anchoring - Xu, F.; Kitzerow, Heinz-Siegfried; Crooker, P. P. (Physical Review E)

A New Method to Align Smectic Liquid Crystals by Photo-Polymerization - Jain, Sukhmal C.; Kitzerow, Heinz-Siegfried (Japanese Journal of Applied Physics)
A novel technique to produce planar and homeotropic alignment of smectic liquid crystals is presented. The technique is based on producing an anisotropic polymer network in the bulk by photo-polymerizing a mixture of photoresist material and liquid crystal by linearly polarized UV-light. Both uniform planar alignment and homeotropic alignment can be obtained depending on the curing conditions. In the case of planar alignment, the orientation of liquid crystal molecules is governed by the direction of the polarization vector of the UV-light, thus making it possible to produce a defined azimuthal orientation of the liquid crystal director. This technique obviates the need to give any previous treatment to the bounding substrates.
Keywords: General Physics and Astronomy; General Engineering

Utility of a liquid crystalline diacrylate for bistable switching cholesteric gel displays - Behrens, Ulrike; Kitzerow, Heinz-Siegfried (Polymers for Advanced Technologies)
Keywords: Polymers and Plastics

Bulk‐induced alignment of nematic liquid crystals by photopolymerization - Jain, Sukhmal C.; Kitzerow, Heinz-Siegfried (Applied Physics Letters)
Keywords: Physics and Astronomy (miscellaneous)

Characterization of Worm-like Micelles Containing Solubilized Dye-Molecules by Light Scattering Techniques - Herzog, Bernd; Huber, Klaus; Rennie, Adrian R. (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

Mixtures of Polyacrylic Acid and Nonionic Surfactants at the Water/Air Interface - Maloney, Colette; Huber, Klaus (Journal of Colloid and Interface Science)
Keywords: Colloid and Surface Chemistry; Surfaces; Coatings and Films; Biomaterials; Electronic; Optical and Magnetic Materials

4. Sonntag nach Trinitatis. Predigttext: 1. Petrus 3,8-15a(15b-17) - Schroeter-Wittke, Harald (Gottesdienstpraxis. Serie A. IV. Perikopenreihe Band 2)

In Bibel steckt Musik. Eine Er-Hörung von 1 Kön 19 - Schroeter-Wittke, Harald (Der Evangelische Erzieher)

Vertical transport studied by sub-picosecond four-wave mixing experiments - Meier, Torsten; Feldmann, J.; von Plessen, G.; Thomas, P.; Göbel, E.O.; Goosen, K.W.; Miller, D.A.B.; Cunningham, J.E. (Coherent Optical Interactions in Semiconductors)
Since the realization of semiconductor heterostructures vertical transport of electrically injected carriers has been one of the most interesting topics in semiconductor physics. Precise engineering of semiconductor layers and thus electronic energy levels allows the tailoring of transport properties over a wide range and has even led to the invention of semiconductor devices relying on ballistic electron transport. In addition, negative differential resistance (NDR) can be realized by using tunneling diodes containing double-barrier heterostructures or a superlattice structure.5,6 Actually, the proposal of Esaki and Tsu5 to use electronic Bloch oscillations in the miniband of a semiconductor superlattice to realize NDR marked the starting point for the physics and applications of semiconductor heterostructures.

Theory of polarization-dependent four-wave mixing using the optical Bloch equations - Meier, Torsten; Bennhardt, D.; Thomas, P.; Hu, Y.Z.; Binder, R.; Koch, S.W. (Coherent Optical Interactions in Semiconductors)
Transient four-wave mixing (TFWM) experiments have been widely used to study the excitation dynamics of excitons in quantum wells [1]. Recently is has been observed that TFWM signals, especially quantum beats between heavy-hole (hh) and light-hole (lh) excitons, strongly depend on the polarization of the incident laser pulses [2–6]. This dependence is presently being investigated.

Contributions of Bound and Unbound Two-Exciton States to the Nonlinear Optical Response of GaAs Quantum Wells - Meier, Torsten; Kuhl, J.; Mayer, E.J.; Smith, G.O.; Bennhardt, D.; Schulze, A.; Thomas, P.; Hey, R.; Ploog, K. (International Conference on Ultrafast Phenomena)
The strong influence of exciton/exciton interaction on the nonlinear optical response of the 2D exciton in GaAs quantum wells has been demonstrated in several recent experimental studies. The theoretical model for the microscopic coupling mechanism is still the subject of controversy, however. In ref. [1], we have presented a model including a density dependent coupling between opposite spin excitons which assumes that the interaction results in a renormalization of the matrix elements, dephasing rates and energies of the transition from the single-exciton state to the two-exciton state with respect to the corresponding quantities for the single exciton transitions. In contrast, Wang et al. claim that all experimental observations are explained by a density induced dephasing rate and that biexciton states play no role [2]. Here we present a new 3-pulse degenerate-four-wave-mixing (DFWM) configuration which is able to differentiate between pure local field effects and biexcitonic contributions to the time-integrated signal. Experiments were performed on an almost homogeneously broadened GaAs/Al0.3Ga0.7As single QW (well width 20 nm, photoluminescence line 0.3 meV, homogenous linewidth 0.15 meV) in the backward reflection geometry. The sample was cooled to 10 K and excited by a sequence of three pulses (1.1 ps duration) with equal intensity, wave vectors 𝑘→1,𝑘→2,𝑘→3 and delays τ12 and τ13 between the second and first and the third and first pulse, respectively. The signal was monitored in the direction 𝑘→𝑠=𝑘→1+𝑘→2−𝑘→3 which provides no signal for the chosen pulse length if local field and renormalization effects are negligible. The peak intensity of the time-integrated DFWM signal has been calculated by solving the optical Bloch for a system of two non-interacting two-level systems (2LS) with opposite circular polarization selection rules (local field effect) and for the renormalized four-level system (4LS) depicted in Fig. 1 which assumes the formation of biexcitons between excitons with opposite spins. The signal strength is proportional to the strength of the local field in the case of the 2LS and to the renormalization for the 4LS. The peak signal intensities expected for pure local field and pure biexction contributions are summarized in the second and third column of Table 1 for eight experimental configurations applying different linear and circularly polarized pulses. The values are normalized to the signal strength predicted for three parallel linearly polarized pulses. Close inspection of the data reveals remarkable differences of the peak amplitude with polarization geometry for the two coupling models.

Polarization selection rules for quantum beating between light and heavy holes in GaAs quantum wells - Meier, Torsten; Mayer, E.J.; Smith, G.O.; Kuhl, J.; Schulze, A.; Bennhardt, D.; Koch, S.W.; Thomas, P.; Hey, R.; Ploog, K. (Proceedings of the 5th European Quantum Electronics Conference)
Several recent experimental and theoretical studies have demonstrated the importance of exciton/exciton coupling due to Coulomb interactions for the nonlinear optical response of the 2D exciton in GaAs quantum wells (QWs).1,2 These results imply that multilevel models are required in order to provide a theoretically appropriate description of the nonlinear behavior. Previous application of a renormalized 9-level system has proven successful in describing the third-order response of hh-excitons in GaAs quantum wells.2 We present a comprehensive experimental and theoretical investigation of the polarization selection rules for degenerate- four-wave-mixing (DFWM) and quantum beating of hh and lh transitions in a GaAs QW. Depending on the polarization and temporal sequence of the three pulses simultaneous excitation of the hh and lh transitions generates either quantum beats (QB), no modulation of the signal, or a superposition of QB and polarization interference (PI) effects as proved by spectrally resolved (SR)-DFWM.

Observation of Biexcitons in Time-Resolved Degenerate-Four-Wave-Mixing on GaAs Quantum Wells - Meier, Torsten; Mayer, E.J.; Smith, G.O.; Kuhl, J.; Bennhardt, D.; Schulze, A.; Thomas, P.; Hey, R.; Ploog, K. (International Conference on Ultrafast Phenomena)
Although the importance of exciton/exciton interactions for the nonlinear optical response of GaAs quantum wells (QW) is well established by many experimental observations, the role of biexciton states in these processes is still an open question, even at low excitation densities. Evidence for the formation of biexcitons has been independently derived from pump-probe studies [1], from the density dependence of the photoluminescence (PL) line shape [2] and from signal modulations observed in degenerate-four-wave-mixing (DFWM) with incoherent light pulses [3]. Here, we report on time-resolved DFWM with parallel (PP) and cross-polarized (CP) pulses. Depending on the polarization geometry, the signals reveal strong quantum beats which correspond to the splitting between either the heavy hole (hh) and light hole (lh) exciton or the hh exciton and the biexciton.

Field-induced dynamics of a wave packet in a wide superlattice miniband - Meier, Torsten; von Plessen, G.; Feldmann, J.; Göbel, E.O.; Thomas, P.; Goossen, K.W.; Kuo, J.M.; Kopf, R.F. (International Quantum Electronics Conference)
In the absence of scattering mechanisms, a crystal electron subjected to a homogeneous electric field undergoes a periodic motion in both momentum and real space. This oscillatory motion is known as Bloch oscillations (BOs) and has recently been detected in transient four-wave mixing (FWM) and Tera-Hertz emission experiments on semiconductor superlattices. It is generally assumed that the minimum field required for the observation of BOs is controlled by the rate of scattering in the material. However, an experimental verification of this point is still lacking.

Direct verification of the existence of biexcitons in GaAs qauntum wells - Meier, Torsten; Smith, G.O.; Mayer, E.J.; Kuhl, J.; Schulze, A.; Bennhardt, D.; Koch, S.W.; Thomas, P.; Hey, R.; Ploog, K. (European Quantum Electronics Conference)
The strong nonlinear optical response of the 2D exciton in GaAs quantum wells at relatively low excitation densities has been observed in many experimental studies in accordance with theoretical predictions. In principle, exciton/exciton interaction results in a renormalization of the transition matrix elements, dephasing rates and frequencies of the excitonic states. Wang et al.1 claimed that all experimental results can be explained by a density- induced enhanced dephasing rate. In a previous paper,2 we have suggested a density dependent coupling between opposite spin excitons, which involves all three renormalization phenomena.